LINGUISTIC FEATURES OF MAGAZINE ADVERTISEMENTS - Abdug’afurova Aziza Shuhratjon qizi, Mastura Mizrobovna Obloqulova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Advertising plays a crucial role in modern marketing, influencing consumer behavior and shaping brand perception. Magazine advertisements, in particular, rely heavily on linguistic techniques to capture readers' attention, evoke emotions, and persuade them to purchase a product or service. This article explores the linguistic features of magazine advertisements, focusing on lexical, syntactic, and rhetorical strategies that advertisers use to engage their target audience.